Epidemiological study of brucellosis and its effect on reproduction failures in dairy cattle in DKI Jakarta - Sudibyo, Agus (Indonesian Journal of Animal and Veterinary Sciences, 1995)
The purposes of this research were to observe prevalence, distribution and reproduction failure evidence of dairy cattle brucellosis in DKI Jakarta . To determine the group of cattle infected with Bntcella abortus, senim and milk samples were carried out . At the beginning, bulk of milk samples were collected from containers . Futhermore, the blood samples were simple randomly collected on cattle that were suspected positive brucellosis in the milk ring test . Those serum samples were tested by using rose bengal plate and complement fixation test . Questioner data in relation with on any reproductive failures, such as abortion, premature dead and born weak, were gathered from farmer within 8 consecutive month period . The result indicate that screening of brucellosis using milk ring test based on bulk milk sample was effective tools to determine the infected group of cattle . The average prevalence of brucellosis in DKI Jakarta area was 4 .5 %. Distribution of brucellosis prevalence were 8 .5% at Setiabudi, 2 .3% at Mampang Prapatan, and 2 .9% at Pasar Minggu . Brucellosis was found at least 201 cattle from 38 dairy cattle farm in DKI Jakarta . Brucellosis was caused abortion about 62 .5% dairy cattle and this value was significantly different than that of uninfected cattle (P<0.05) . Brucellosis also cause stillbirth around 9 .8% and born weakness 15 .2% . The widely distributed and high prevalence brucellosis of dairy cattle in DKI Jakarta was influenced by uncontrol of cattle movement and high abortion cases rate . Keywords : Brucellosis, epidemiology, dairy cattle, DKI Jakarta